Revision of the genus Tubulariella P.C. Silva (Bacillariophyta) - Williams, David M.; Sims, Pat A. (Phytotaxa, 2026)
A review of species currently placed in the genus Tubulariella P.C.Silva (=Tubularia Brun) is provided. Three species are discussed: Tubulariella pistillaris, T. tabellarioides and an unnamed taxon as no specimens for light microscopy are available. Comments are made on additional specimens that may or may not belong to Tubulariella. The relationships of Tubulariella are discussed.